Educação empreendedora: perspectivas de profissionais da área de Visagismo - Trindade, Robson Amauri (2019)
The general objective of this research is to study how visagist professionals understand the main concepts involving entrepreneurial education and the entrepreneurial skills of the 21st century, as well as their perspectives in relation to this theme in the respective area. What justifies this research is that although several scholars understand that the visagism can be a valuable tool of simulation and construction of new images, there is a shortage of academic research on the insertion of the visagism in the adaptation of images constructed in the day to day of people. In view of the objectives (general and specific) we consider the following problematizing question: how do teachers of the area of visagism understand and seek to put into practice the main concepts related to entrepreneurial education and entrepreneurial skills of the 21st century? This research is conducted according to the exploratory approach, of a qualitative nature. Although many researchers make an option to direct their work towards a more qualitative or quantitative approach, others have suggested combining two or more research methods